2021
DOI: 10.21203/rs.3.rs-184446/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic analyses of 10,376 individuals provides comprehensive map of genetic variations, structure and reference haplotypes for Chinese population

Abstract: Here, we initiated the Westlake BioBank for Chinese (WBBC) pilot project with 4,535 whole-genome sequencing individuals and 5,481 high-density genotyping individuals. We identified 80.99 million SNPs and INDELs, of which 38.6% are novel. The genetic evidence of Chinese population structure supported the corresponding geographical boundaries of the Qinling-Huaihe Line and Nanling Mountains. The genetic architecture within North Han was more homogeneous than South Han, and the history of effective population siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Gene enrichment analysis also supported the most enrichment related to the human immune response in terms of cellular component and molecular function. The positive selective sweeps in this region have been already identified in Han populations (Zheng et al, 2021). However, the alcohol dehydrogenase (ADH) gene cluster that underwent regional selective sweeps in East Asia (Ma et al, 2005;Li et al, 2008;Li et al, 2011;Allentoft et al, 2015) was not identified, and the derived allele frequency of ADH genes in three Mongolian subgroups showed a strong correlation with the genetic affinity to Han, indicating the possibility of introducing genes into Mongolians.…”
Section: Discussionmentioning
confidence: 99%
“…Gene enrichment analysis also supported the most enrichment related to the human immune response in terms of cellular component and molecular function. The positive selective sweeps in this region have been already identified in Han populations (Zheng et al, 2021). However, the alcohol dehydrogenase (ADH) gene cluster that underwent regional selective sweeps in East Asia (Ma et al, 2005;Li et al, 2008;Li et al, 2011;Allentoft et al, 2015) was not identified, and the derived allele frequency of ADH genes in three Mongolian subgroups showed a strong correlation with the genetic affinity to Han, indicating the possibility of introducing genes into Mongolians.…”
Section: Discussionmentioning
confidence: 99%